The Effects Of Stichopus Variegatus Crude Extracts On Acute Contusive Rat Spinal Cord Injury Model : In Vitro And In Vivo Studies - Ab Patar, Mohd Nor Azim (2012)
Sea cucumbers from Pulau Perhentian, Malaysia are well known as potential marine edible food sources and possess medicinal value to the Malaysian community. Despite the presence of small industries and its usage amongst local folks, there is little work done on its biological activity, especially on the central nervous system. In the present study, Stichopus variegatus (SV) were harvested, processed and extracted in the laboratory and were evaluated on their proliferative activity on rat astrocytes cell lines (in vitro), as well as contusive spinal cord injury in a rat model (in vivo). In vitro analysis of SV extract showed proliferative activity of rat astrocytes cell line at 5 μg/ml and 10 μg/ml.